2005
DOI: 10.1094/mpmi-18-0694
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trehalose Transport and Utilization in Sinorhizobium meliloti-Alfalfa Interactions

Abstract: Genes thuA and thuB in Sinorhizobium meliloti Rm1021 code for a major pathway for trehalose catabolism and are induced by trehalose but not by related structurally similar disaccharides like sucrose or maltose. S. meliloti strains mutated in either of these two genes were severely impaired in their ability to grow on trehalose as the sole source of carbon. ThuA and ThuB show no homology to any known enzymes in trehalose utilization. ThuA has similarity to proteins of unknown function in Mesorhizobium loti, Agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
56
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 57 publications
5
56
0
Order By: Relevance
“…The biochemical functions of the thuAB genes are currently unknown. As reported in our earlier study (20), we were also unable to detect glucose as a product of trehalose catabolism in S. meliloti. We have also been consistently unsuccessful in our attempts to detect other known intermediates of trehalose breakdown, such as glucose-6-phosphate, in reaction mixtures containing trehalose and induced S. meliloti cells or cell extracts, through thin-layer chromatography (TLC), HPLC, or HPLC-MS (results not presented).…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The biochemical functions of the thuAB genes are currently unknown. As reported in our earlier study (20), we were also unable to detect glucose as a product of trehalose catabolism in S. meliloti. We have also been consistently unsuccessful in our attempts to detect other known intermediates of trehalose breakdown, such as glucose-6-phosphate, in reaction mixtures containing trehalose and induced S. meliloti cells or cell extracts, through thin-layer chromatography (TLC), HPLC, or HPLC-MS (results not presented).…”
Section: Resultssupporting
confidence: 57%
“…We have reported that in S. meliloti, the thu operon (thuEFGKAB) is the major system for the transport and utilization of the disaccharide trehalose (19)(20)(21). The entire thu operon is also present in similar organizations with various degrees of homology and identity in the sequenced genomes of several other members of the Rhizobiaceae, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of the thuA, thuE, and thuG genes was also observed upon an osmotic upshift. These genes are part of a cluster of six genes involved in trehalose transport and utilization (25,26).…”
Section: Resultsmentioning
confidence: 99%